Greening our economy for a sustainable future - Grima, Simon; Sood, Kiran; Ozen, Ercan; Dalli Gonzi, Rebecca Emily (Science of sustainable systems, 2025)
Greening Our Economy for a Sustainable Future examines the green economy by balancing social needs, the environment, and the economy. It argues that different economic models must be developed to address the environment caused by economic expansion. The book not only looks at the opportunities of having a green economy, but also goes into areas such as greenwashing, social washing, sustainability, economics, and more. In addition, it addresses how one can improve well-being through a symbiotic relationship between economic growth and environmental stewardship.